Engineering practice in a global context understanding the technical and the social - Williams, Bill 1947-; Figueiredo, José; Trevelyan, James P. (CRC Press/Balkema, 2013)
"This book characterizes the technical and social aspects of engineering practice and to look at ways that this characterization can be important in the design of engineering courses in higher education. The principal contours of the work include the study of engineering practice and its relation to knowledge, competences and to crossdisciplinary and identity contexts. Empirical data on the practice of engineering professionals are presented from a range of companies in different national contexts, including engineering design companies and engineering innovation leaders"